PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN ILMU PENGTAHUAN ALAM MENGGUNAKAN TIPE JIGSAW DI KELAS IV - Kasyadi, Yahyo; Kresnadi, Hery; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem of this research is how to improve student learning outcomes by using jigsaw on Natural Science learning in grade IV Pontianak Utara? The purpose of this study is to improve student learning outcomes on learning Natural Science by using jigsaw in class IV. The research method used is descriptive research method. The study consisted of two cycles and each cycle consisted of planning, action, observation, reflection. The results of the study were as follows: (1) Teacher improvement in learning plan on cycle I 3.77 and cycle II 3.95 with an average increase of 0.18. (2) Teacher improvement in learning in cycle I 3.39 and cycle II 3.74 with an average increase of 0.35. (3) Increased student learning outcomes, average cycle I 72.78 and cycle II 83.33 with an average increase of 10.56. There is an increase in student learning outcomes in student learning using jigsaw in grade IV Sekiolah Dasar Negeri 40 Pontianak Utara.Â Keywords: Student Learning Outcomes, Natural Sciences, and Jigsaw TypeÂ